Progress in EUV lithography toward manufacturing - Kim, Seong-Sue; Chalykh, Roman; Kim, Hoyeon; Lee, Seungkoo; Park, Changmin; Hwang, Myungsoo; Park, Joo-On; Park, Jinhong; Kim, Hocheol; Jeon, Jinho; Kim, Insung; Lee, Donggun; et al. (SPIE, 2017)
In this article the recent progress in the elements of EUV lithography is presented. Source power around 205W was demonstrated and further scaling up is going on, which is expected to be implemented in the field within 2017. Source availability keeps improving especially due to the introduction of new droplet generator but collector lifetime needs to be verified at each power level. Mask blank defect satisfied the HVM goal. Resist meets the requirements of development purposes and dose needs to be reduced further to satisfy the productivity demand. Pellicle, where both the high transmittance and long lifetime are demanded, needs improvements especially in pellicle membrane. Potential issues in high-NA EUV are discussed including resist, small DOF, stitching, mask infrastructure, whose solutions need to be prepared timely in addition to high-NA exposure tool to enable this technology.